The Contribution of Rivers to the Development of Circular Tourism Case Study: The Acheron River in Greece - Economou, Agisilaos (European Journal of Applied Sciences, 2022)
The present paper investigates the contribution of a river to the development of circular tourism in a place and specifically, a region. According to historical data, it has been proven that human societies tended to look for areas with rich natural resources to develop. These areas were traditionally selected because of the sustainability of these resources. Especially those areas that are located near rivers also had the advantages of moving people and products, fishing and the availability of water. The following text highlights the possibilities that exist for the utilization of riparian sites for the circular tourist development. The Acheron River in the Region of Epirus in Greece is selected as a case study. To serve the purpose, a questionnaire was constructed which was addressed to 352 visitors / tourists in the research area. The work concludes with conclusions and proposals regarding the development of circular tourism in this area.